Literasi Digital Mahasiswa Ilmu Komunikasi Universitas Muhammadiyah Bengkulu Dalam Mengidentifikasi Hoaks Pada Instagram - Suci Rahmadani (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2025)
This research explores how Generation Z students at Universitas Muhammadiyah Bengkulu adapt to the challenge of recognizing hoaxes on Instagram within the framework of digital media literacy. The main objective is to identify the strategies they use to verify information, the barriers they face, and how the four pillars of media literacy access, analysis, evaluation, and creation are reflected in their digital practices. The study applies a qualitative design, employing in depth interviews, non-participant observation, and analysis of personal documents. Two students were deliberately chosen through purposive sampling because of their engagement in academic organizations and digital literacy communities. Data were processed using thematic analysis to interpret their approaches to information verification and online interaction. The results indicate that participants actively perform cross checking across multiple platforms, seek validation from trusted communities or public figures, and examine visual elements before confirming content. Despite these strategies, they continue to face difficulties such as reliance on cognitive shortcuts, exposure to algorithm-driven content, and the rise of advanced digital manipulation like deepfakes. The findings confirm that, although Generation Z demonstrates strong technological proficiency, their capacity for critical evaluation remains insufficient.